Linking metabolic and contractile dysfunction in aged cardiac myocytes. Issue 20 (30th October 2017) - Barton, Gregory P.; de Lange, Willem J.; Ralphe, John C.; Aiken, Judd; Diffee, Gary
Abstract: Aging is associated with declining cardiac contractile function as well as changes in metabolism and mitochondrial function. The relationship between age‐related changes in cardiac metabolism and declining cardiac contractile function has not been determined. In order to define the role energetics play in changes in contractile function, we measured mitochondrial NADH, [NADH]m, during continuous contractions of isolated left ventricular myocytes from young (Y) and old (O) FBN rats. Second, we explored the role of metabolic disruption with rotenone and increased workload with isoproterenol (ISO) had on age‐related changes in myocytes shortening. Single, intact myocytes were stimulated for 10 min of continuous contraction at either 2 Hz or 4 Hz while being perfused with Ringer's solution. Properties of shortening (peak shortening and rate of shortening) were measured at the onset (T0) and after 10 min (T10) of continuous contraction, and the decline in shortening over time (T10/T0) was determined. Although young and old myocytes had similar contractile function under resting conditions, old myocytes demonstrated decrements in [NADH]m during continuous stimulation, while young myocytes maintained constant [NADH]m over this time. In addition, old myocytes exhibited impaired contractile function to a workload (ISO) and metabolic (rotenone) stress compared to young myocytes. Taken together, these results demonstrated that old myocytes are susceptible to stress‐induced contractile dysfunction which may be related to altered cellular energetics. Abstract : Aging is associated with declining cardiac contractile function as well as changes in metabolism and mitochondrial function. The purpose of this study was to examine the relationship between age‐related changes in cellular metabolism and contractile function. Our results demonstrate stress‐induced contractile dysfunction in aged myocytes which may be related to altered cellular energetics.